PENGEMBANGAN KISI-KISI SOAL IPAS BERBASIS MEANINGFULL LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V ORGAN TUBUH MANUSIA - Yetty Sari; Rida Fironika Kusuma Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a blueprint of IPAS test items based on Meaningful Learning for the topic of human body organs in fifth-grade elementary school that is valid and practical. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study included two expert lecturers and one teacher as validators, as well as five fifth-grade teachers as respondents for the practicality test. The research instruments consisted of interview guidelines, expert validation sheets, and teacher practicality questionnaires. The validation process assessed the suitability of content, conceptual understanding indicators, integration of Meaningful Learning principles, construction, and language aspects. The results showed that the developed blueprint achieved a feasibility percentage of 93.3%, categorized as very valid. The practicality test results indicated an average score of 3.57, categorized as very practical. These findings indicate that the Meaningful Learning-based test blueprint is appropriate to be used as a systematic guide in constructing assessment instruments oriented toward students’ conceptual understanding. The developed product is expected to support the implementation of IPAS assessment aligned with meaningful learning principles and the Merdeka Curriculum demands.